Quantitative and qualitative studies of extrinsic and intrinsic uniformity on gamma camera detectors using co-57 flood source & tc-99m point source: experimental and clinical studies - Yuan, Koo Xing (Universiti Sains Malaysia, 2024)
Background: Quality control tests, such as uniformity tests, ensure optimal operation of gamma cameras by evaluating the detectors’ response to a spatially uniform photons flux across the field of view (FOV). Daily uniformity tests include extrinsic and intrinsic types. Methods: A Cobalt-57 flood source was used for the extrinsic test, and a Technetium-99m point source (0.8 mCi) for the intrinsic test. Background counts were measured without the source. For extrinsic test, data acquisition for both detectors was done using a 256 x 256 matrix with 5 million total counts at source-to-collimator distances of 5 cm, 10 cm, and 15 cm for the extrinsic test, and at source-to-detector distances of 2FOV, 3FOV, and 4FOV for the intrinsic test. Data analysis using Xeleris Workstation involved creating regions of interest within full, useful, and central FOV to measure mean counts and calculate signal-to-noise (SNR) and contrast. The Kruskal-Wallis H test assessed associations between SNR, contrast and varying distances. Qualitative assessments were made by one expert observer and three peer observers acquired for extrinsic images at 10 cm and intrinsic images acquired at 4FOV. Five clinical bone images were reviewed for artifacts. Result: For the extrinsic test, SNR and contrast slightly decreased in both the UFOV (SNR: 124.603 to 124.263; contrast: 151.282 to 150.869) and CFOV (SNR: 124.401 to 123.611; contrast: 151.036 to 150.077) of Detector 1 with increased source-to-collimator distances. For the intrinsic test, SNR and contrast in all FOVs were the lowest at 2FOV. For both tests, quantitative analysis showed no statistically significant differences in SNR and contrast at varying distances within each FOV (p > 0.05) for both detectors. Qualitatively, nonuniformity was inspected in the extrinsic images at 10 cm (mean visual score= 2.75), showing photomultiplier tubes (PMTs) pattern, whereas no nonuniformities were visible in intrinsic images at 4FOV (mean visual score= 1). Clinical images revealed artifacts due to patient-related factors but no gamma camera-related artifacts. Conclusion: There was no significant association between the extrinsic and intrinsic uniformity of gamma camera detectors and different distance (p > 0.05). PMTs artifacts observed in the extrinsic test were not seen in clinical images, suggesting they might result from low energy of Co-57, impurities, collimator septa penetration, or photon scattering rather than gamma camera malfunctions.